Rotordynamic modelling and analysis of a radial inflow turbine rotor-bearing system - Jung, Hyung-Chul; Krumdieck, S. (Springer, 2014)
One of the challenging aspects of radial turbine design and manufacturing is vibration and stability. Rotordynamic analysis was performed on a rotor-bearing system of a 1 kWe radial inflow turbine. The objective of rotordynamic analysis is to determine suitable system configuration for stable operation in the design process. The rotor and blade design were previously developed using ANSYS Structural module which provides the mass and inertia of the complex blade geometry for the rotordynamic analysis. A simulation model with concentrated mass and inertia was built for the rotating structure using ANSYS Parametric Design Language (APDL). Modal and mass unbalance response analyses were carried out with six cases having different shaft diameters and bearing arrangements. The best case was chosen for further parametric study of the effects of shaft length, blade residual unbalance, and bearing stiffness on the blade displacement amplitude. Blade clearance was then set to determine acceptable shaft length, bearing arrangement, blade unbalance quality, and bearing stiffness.